A Tourist Region — A New Meanning in an Old Form? - Bachvarov, Marin (Turyzm/Tourism, 2003)
The article is an attempt to explain the meaning and possible applications of the term 'region', with reference to tourist régionalisation and in comparison with existing theory on the subject. The author analyses both the specific features of a tourist region and the relation between a region and the recreational-tourist system. A tourist region is both a sector and funcUonal system at the same time. The author discusses the delimitation of a tourist region and briefly presents the régionalisation problems raised in Polish academic literature. He also attempts to answer the question of why specialists are not interested in tourist régionalisation.